Color stabilization of green vegetables at storage - Прісс, Олеся Петрівна; Кулик, Аліна Степанівна (Eastern-European Journal of Enterprise Technologies, 2014)
The effect of antioxidant preparations on color changes during storage of parsley, cucumbers and zucchini was investigated. The application of antioxidants is proposed to delay dissociation of chlorophylls, carotenoids and maintain high quality of green vegetables. Postharvest heat treatment by antioxidant solution which contains chlorophilipt for cucumbers and zucchini is recommended. The nutrient solution with antioxidants based on hydrogel may be used for parsley. It was established that the use of complex antioxidant composition of chlorophyllipt promotes certain stabilization of color during parsley, cucumbers and zucchini storage. It is shown that the application of nutrient solution with the addition of antioxidants can reduce the rate of chlorophyll destruction up to 1.1 ... 1.6 times and carotenoids destruction up to 1.2 ... 1.6 times according to the season of cultivation and varieties of parsley. After using the antioxidant composition for cucumber treatment there is a statistically significant decrease in the concentration of chlorophylls comparing with the initial value. It was detected after 21 days storage. The concentration of carotenoids in experimental cucumbers at the end of storage is 21 to 23 percent more than it is in the control ones. Antioxidant treatment also reduces the chlorophylls and carotenoids degradation in zucchini.